On Ibn Khaldun’s critical thinking: conceptual framework - Salah, Machouche; Bensaid, Benaouda (2012)

(untitled)
Significant research has been made to understand the thought and contributions of Ibn Khaldun to various branches of human knowledge including philosophy of history, historiography, politics, economics and education. Weak interest however, is shown to his contribution to the theory of human thinking. This research investigates Ibn Khaldun’s perspective on critical thinking, and his critic of some sciences known in his time. This inquiry examines the origin and some of the dimensions of critical thinking as experienced and developed by Ibn Khaldun while highlighting the religious and epistemological factors required to develop potential ability leading to the practice of critical thinking. This research draws on Ibn Khaldun’s writing as well as the contemporary studies, particularly those concerning Ibn Khaldun critical thinking and its epistemological implications.